Frequency of Fungal Infection in Histopathological Sections of Patients Undergoing Functional Endoscopic Sinus Surgery for Sinonasal Disease (Journal of Fatima Jinnah Medical University, 2025)
ABSTRACTBackground: Fungal rhinosinusitis can occur in different sinonasal conditions. It seemed to be present in 1-18% of these patients. Due to the warm and humid environment of the sinonasal cavity, combined with underlying nasal conditions such as chronic sinusitis and nasal polyposis, these patients are at risk of developing fungal infections. The objective of this study was to find out the frequency of fungal infection in histopathological sections of patients who had underwent functional endoscopic sinus surgery for sinonasal diseases.Methods: A retrospective clinical record review study conducted at the Department of Ear, Nose, and Throat (ENT) of Shifa Foundation Clinic and Shifa International Hospital from August 2018 to January 2024. Total 304 patients who underwent functional endoscopic sinus surgery (FESS) over a period of 6 years, with diagnosis of sinonasal disease established through clinical evaluation and imaging studies prior to surgery, and histopathology reports generated from surgical specimens obtained during the surgery. The surgical specimen was prepared as per the recommendation of the microbiology department of the institutions. The data was analyzed in SPSS to find the frequency of fungal infections.Results: Out of 304 subjects, 62.5% were male and 37.5% female. The study analyzed histopathology reports of patients diagnosed with various nasal and sinus conditions. The most common diagnosis was inflammatory nasal polyps 222 cases (73%), followed by fungal infection with 21 cases (6.9%) and acute on chronic inflammation 20 cases (6.6%). The results indicate a high incidence of inflammatory conditions in the nasal and sinus regions.Conclusion: This study provides fungal infiltration is detected in moderate samples obtained during functional endoscopic sinus surgery.
Keywords: Sinusitis; Paranasal sinus diseases; Mycoses; Morphological spectrum, Intranasal polyps, Histopathology.